Behavior and damage of a pipe in the presence of a corrosion defect depth of 10% of its thickness and highlighting the weaknesses of the ASME / B31G method - H. Berrekia; D. Benzerga; A. Haddi (Fracture and Structural Integrity)
The company DRC (pipe repair Department) located within the SONATRACH Company of oil and gas in Algeria, which is responsible for the repair of pipelines for the transport of gas or crude petroleum, will rehabilitate old pipes that have operated on-line for approximately 30 years or come from remaining projects. On the assumption that rehabilitating a pipeline means making it workable under the same conditions as a new structure and reducing the overall cost of the project. The abandonment of these tubes will have an important environmental and financial impact. The rehabilitation, which consists of recovering the maximum of tube, already used, therefore reduces the cost of the project. Inspection and evaluation of corrosion defects are carried out in accordance with ASME/31G method that is applied to low alloyed carbon steels with corrosion defects having soft profiles with low stress concentration. Our research will consist in developing a method using a behavior-damage coupling of the material to highlight the weaknesses of the ASME / B31G method [1] and show for defects whose depth does not exceed 10%, these defects can survive hydrostatic testing but will develop during service when the pressure is variable.